2008
DOI: 10.1093/ndt/gfn585
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated compensatory response to acute respiratory alkalosis in panic disorder is induced by increased lactic acid production

Abstract: These results suggest that the compensatory metabolic response to acute respiratory alkalosis is exaggerated by increased lactic acid production in panic disorder patients. Here, we call attention to the diagnosis of acid-base derangements by means of plasma [HCO(3)(-)] and lactate concentration in panic disorder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…Increased lactate serum concentration changes other parameters of acid-base status, particularly the consumption of bicarbonates with the consequent increase in base deficit ( 19 ). Higher base deficit in patients with hemodynamically stable PE in our study was a result of increased lactate level and the presence of metabolic lactic acidosis with the respiratory disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Increased lactate serum concentration changes other parameters of acid-base status, particularly the consumption of bicarbonates with the consequent increase in base deficit ( 19 ). Higher base deficit in patients with hemodynamically stable PE in our study was a result of increased lactate level and the presence of metabolic lactic acidosis with the respiratory disorder.…”
Section: Discussionmentioning
confidence: 99%
“…16, 21 In addition, neuroimaging studies also raise the possibility of dysregulated acid–base buffering and increased plasma and brain lactate responses to metabolic challenges in PD. 22, 23, 24 There is also a high prevalence of hyperventilation and other respiratory abnormalities among patients with PD. 21, 25, 26 The link between panic attacks and pH disturbances also forms the basis of the false suffocation alarm theory of spontaneous panic, where CO 2 hypersensitivity may exist due to a malfunctioning suffocation alarm monitor.…”
Section: Acidosis An Interoceptive Trigger In Panic: Evidence For Rementioning
confidence: 99%
“…Variables with dichotomous outcomes (e.g., sex) were evaluated using Fisher's exact test. As the previous study had shown that the correlation between PCO 2 and lactate was not linear, Spearman's rank correlation coefficient (ρ) was calculated to assess the associations between serum lactate level and pH, PCO 2 , or in each study group (ABG and VBG analysis) [2,4]. Using the same procedure, we conducted a sensitivity analysis using…”
Section: Discussionmentioning
confidence: 99%
“…Studies of arterial blood gas (ABG) analysis in patients with psychogenic hyperventilation have shown an inverse correlation between the arterial partial pressure of carbon dioxide (PaCO 2 ) and the serum lactate level [2,4].…”
Section: Hco −mentioning
confidence: 99%